Study of hybrid optical burst switching networks - PENG Peng; PAN Yu-yan; WANG Jun-feng; LIN Jin-tong (Tongxin xuebao)
The hybrid optical burst switching （HOBS） was proposed, and investigate the HOBS based a ring topology with numerical simulation. Results indicate that the packet lost ratio in HOBS is much less than that in OBS, and its performance depends on some parameters such as the packet proportion, the electronic buffer size and the processing speed in node.